Faktor Yang Berhubungan Dengan Waktu Tunggu Pasien Pada Bagian Farmasi Di Rsu. Mitra Medika - Manisha Manisha; Rida Dwi Andriyani; Muhammad Adiul Ilham (Jurnal Kesehatan dan Fisioterapi, 2021)
Waiting time is the minimum standard for pharmacy services in hospitals that must be evaluated to improve the quality of excellent service. Pharmacy installations have a minimum service standard where officers can complete prescriptions for 60 minutes and non-concoctions for 30 minutes. Purpose: To determine the factors associated with waiting time in the pharmacy division at Mitra Medika Hospital Tanjung Mulia in 2021. Methd: Used quantitative research with a Cross-Sectional approach. The population was 28 respondents. The sample was taken from the entire population in pharmacy installation. The technique of data analysis used Univariate and Bivariate. Result: It showed the relationship of Human Resources with the waiting time at the pharmacy with a p-value of 0.000<.05, the Availability of the Drug with the waiting time with a p-value of .006<.05, the Means and Infrastructure with the waiting time with a p-value .003<.05. Conclusion: there is a relationship between waiting time at the pharmacy by human resources, availability of drugs, facilities, and infrastructure in Mitra Medika Hospital Tanjung Mulia. It is suggested to increase the number of officers in pharmaceutical, so the time required is balanced with the officer, attention to the time of booking until the drug is received so as not to excess or less, and more number of computers and a table of compounding so that the officer is quick to prepare recipes of the drug.Keywords: Waiting Time, Human Resources, Availability of Drugs, Facilities, Infrastructure